Unnatural history [large type] - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels, 2023)
"Los Angeles is a city of stark contrast, the palaces of the affluent coexisting uneasily with the hellholes of the mad and the needy. It is that shadow world and the violence it breeds that draw brilliant psychologist Dr. Alex Delaware and Detective Milo Sturgis into an unsettling case of altruism gone wrong. On a superficially lovely morning a woman shows up for work with her usual enthusiasm. She's the newly hired personal assistant to a handsome, wealthy photographer and is ready to greet her boss with coffee and good cheer. Instead, she finds him slumped in bed, shot to death. The victim had recently received rave media attention for his latest project: images of homeless people in their personal 'dream' situations, elaborately costumed and enacting unfulfilled fantasies. There are some, however, who view the whole thing as nothing more than crass exploitation, citing token payments and the victim's avoidance of any long-term relationships with his subjects. Has disgruntlement blossomed into homicidal rage? Or do the roots of violence reach down to the victim's family--a clan, sired by an elusive billionaire, that is bizarre in its own right? Then new murders arise, and Alex and Milo begin peeling back layer after layer of intrigue and complexity, culminating in one of the deadliest threats they've ever faced" --